Peran Guru Agama Katolik dalam Meningkatkan Motivasi Belajar Peserta Didik Kelas VIII SMP Negeri 2 Wulandoni - Keta, Maria Aprilia Ansi; Victoria, Maria Anggela (Vocat : Jurnal Pendidikan Katolik, 2023)
The duties and roles of the teacher are a unified whole. It's just that sometimes the tasks and functions are equated as an elaboration of roles. The role of the teacher includes: educating, guiding, training, advising, reforming, being a model and role model, having personality, researcher, encouraging creativity, arousing views, doing routine work, moving camps, telling stories, being an actor, emancipator, preserving, as a culminator , and evaluate. The role of the teacher in educational development includes: inculcating values, building character, central to learning, providing assistance and encouragement, supervising and coaching, disciplining children, and being a role model for the environment. This research raises questions such as; What can influence the learning motivation of class VIII students of SMP Wulandoni to study? What is the strategy used by the teacher to increase the learning motivation of class VIII students at SMP Wulandoni? The aims of this study were: to describe the influence of the learning motivation of class VIII students at SMP Wulandoni and to describe the role of the teacher in increasing the learning motivation of class VIII students at SMP Wuladoni. The type of research used in this research is descriptive with a qualitative approach. The descriptive research used in this study is intended to describe the teacher's role in increasing learning motivation in class VIII students of SMP Wulandoni. The results of the research showed that the things that can affect the learning motivation of class VIII students at Wulandoni Middle School and the role of the teacher in increasing student learning motivation is by using interesting learning media, choosing the right learning method, and creating competition and student cooperation. The results of this study can be concluded that there are some students who have an intention in learning, so that the strategy carried out by the teacher is quite advanced.